2018
DOI: 10.1016/j.dib.2018.08.191
|View full text |Cite
|
Sign up to set email alerts
|

Data on expenditure, revenue, and economic growth in Nigeria

Abstract: This article describes the data for examining the influence of government expenditure and revenue on Nigerian economic growth. Data were extracted from the World Bank database and Central Bank of Nigeria (CBN) Statistical bulletin. The data are available with this article. The data is related to the research article “Newly proposed estimator for ridge parameter: an application to the Nigerian economy” (Lukman and Arowolo, 2018) but not discussed in detail. This data article will assist economists in identifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 2 publications
3
5
0
2
Order By: Relevance
“…For instance, Khandker (2005) in a study using panel data from Bangladesh found that access to microfinance helped to alleviate poverty in rural communities in Bangladesh. Similar studies by Lashley (2004) in the Carribean, Akanji (2006) in Nigeria, Imai et al (2010) in India, Nawaz (2010) in Bangladesh, Montgomery and Weiss (2011) in Pakistan and Okibo and Makanga (2014) in Kenya all came to the same conclusion that microfinance is a veritable tool to alleviate poverty by empowering the poor and supporting incomegenerating activities of households especially those in the rural areas.…”
Section: Conceptualisation Of the Shockfrom Covid-19supporting
confidence: 55%
“…For instance, Khandker (2005) in a study using panel data from Bangladesh found that access to microfinance helped to alleviate poverty in rural communities in Bangladesh. Similar studies by Lashley (2004) in the Carribean, Akanji (2006) in Nigeria, Imai et al (2010) in India, Nawaz (2010) in Bangladesh, Montgomery and Weiss (2011) in Pakistan and Okibo and Makanga (2014) in Kenya all came to the same conclusion that microfinance is a veritable tool to alleviate poverty by empowering the poor and supporting incomegenerating activities of households especially those in the rural areas.…”
Section: Conceptualisation Of the Shockfrom Covid-19supporting
confidence: 55%
“…But of course, in a fair way, bank credit or macro debt will also have a negative impact, for example, it will put pressure on the tax sector that is increasingly large and massive to balance the debt position, and is feared to have an effect on fiscal, monetary, and state strategic policies. Wisely and ideally to overcome the adverse effects of the high debt burden in the form of credit banks in Indonesia, the government regulation policy is sought and maximized so that the debt function becomes effective as suggested in the study (Roşoiu, 2015;Sangha et al, 2019;Lukman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, for the energy sector and energy policy, government spending in this sector has a significant role in terms of economic growth (Fizaine & Court, 2016), as well as government policy (Roşoiu, 2015), public welfare (Sangha et al, 2019) and level of national income (Lukman et al, 2018).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…IBM Statistical Package for Social Sciences (IBM 20) was used to analyze the data of the scholastic performance of students in 12 programs at the College of Science and Engineering within the year 2010 to 2014. The statistical methodology includes regression analysis, analysis of variance (ANOVA), and descriptive statistics ( Lukman et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%